Survival Signaling by C-RAF: Mitochondrial Reactive Oxygen Species and Ca(2+) Are Critical Targets - Kuznetsov, Andrey V. (American Society for Microbiology (ASM), 2008)
Survival signaling by RAF occurs through largely unknown mechanisms. Here we provide evidence for the first time that RAF controls cell survival by maintaining permissive levels of mitochondrial reactive oxygen species (ROS) and Ca(2+). Interleukin-3 (IL-3) withdrawal from 32D cells resulted in ROS production, which was suppressed by activated C-RAF. Oncogenic C-RAF decreased the percentage of apoptotic cells following treatment with staurosporine or the oxidative stress-inducing agent tert-butyl hydroperoxide. However, it was also the case that in parental 32D cells growing in the presence of IL-3, inhibition of RAF signaling resulted in elevated mitochondrial ROS and Ca(2+) levels. Cell death is preceded by a ROS-dependent increase in mitochondrial Ca(2+), which was absent from cells expressing transforming C-RAF. Prevention of mitochondrial Ca(2+) overload after IL-3 deprivation increased cell viability. MEK was essential for the mitochondrial effects of RAF. In summary, our data show that survival control by C-RAF involves controlling ROS production, which otherwise perturbs mitochondrial Ca(2+) homeostasis.